ANALISIS PELAKSANAAN STRATEGI PENINGKATAN PENERIMAAN PAJAK REKLAME PADA UNIT PELAYANAN PAJAK DAN RETRIBUSI DAERAH CEMPAKA PUTIH TAHUN 2014-2016 - Tirza Aditya; Chairil Anwar Pohan (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
This research aims to determine the implementation of the strategy for increasing advertisement tax revenue, to find out any problems found by the unit of tax service and regional restitution, and to resolve the problem on its implementation. This research uses descriptive type and qualitative approach. Data collection techniques uses for this research is interviews, observation and documentation. Conclusion research strategy of the increased in revenue advertisement tax in tax service unit and levies cempaka putih central jakarta not yet optimal because there are still many taxpayers who have not list repeated, lack of the expansion of taxpayers new, human resources not effective, lack of taxpayers who has not done their obligations, not fully sanstions applied because it is still the weak supervision. Advice research strategy of the increased in revenue advertisement tax in the service taxes and levies dae service unit.